Key engineering materials IX : 9th International Conference on Key Engineering Materials (9th ICKEM 2019) - Korsunsky, Alexander (Key engineering materials, 2019)
The collected papers are focused on research in the areas of biomaterials, novel composite and polymer materials, ceramics, steel, alloys, building materials, materials processing technology, material performance analysis, and engineering evaluation. Biomaterials, Hydroxyapatite, Hydrogel, Biocomposite, Composites, Nanocomposites, Graphene, Polymers, Steel, Alloys, Microstructure, Ceramics, Semiconductors, Additive Manufacturing, Corrosion, Protective Coatings, Chemical Processing, Fuel Cell, Polymer Electrolyte, Solid State Synthesis, Building Materials, Environmental Engineering Materials Science, Building Materials, Mechanical Engineering.